Transcriptome analysis reveals the mechanism for blue-light–induced biosynthesis of delphinidin derivatives in harvested purple pepper fruit - Gao, Jinhui; Dou, Yuwei; Wang, Xiaotong; Zhang, Dalong; Wei, Min; Li, Yan (Frontiers in Plant Science, 2023)
Anthocyanins are the main pigments that affecting the color and quality of purple-fruited sweet pepper (Capsicum annuum). Our previous study indicated that blue light can induce anthocyanin accumulation in purple pepper. In view of its underlying mechanism is unclear, here, anthocyanin content was determined, and transcriptome analysis was performed on pepper fruits harvested from different light treatments. As a result, among the identified anthocyanin metabolites, the levels of delphinidin (Dp) glycosides, including Dp-3-O-rhamnoside, Dp-3-O-rutinoside and Dp-3-O-glucoside were highly accumulated in blue light-treated fruit, which are mainly responsible for the appearance color of purple pepper. Correlation between anthocyanin content and transcriptomic analysis indicated a total of 1,619 up-regulated genes were found, of which, 6 structural and 12 transcription factor (TF) genes were involved in the anthocyanin biosynthetic pathway. Structural gene, for instance, CaUFGT as well as TFs such as CaMYC2-like and CaERF113, which were highly expressed under blue light and presented similar expression patterns consistent with Dp glycosides accumulation, may be candidate genes for anthocyanin synthesis in response to blue light signal.